2021
DOI: 10.1016/j.cmi.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Upper respiratory tract SARS-CoV-2 RNA loads in symptomatic and asymptomatic children and adults

Abstract: Objectives Studies comparing SARS-CoV-2 RNA load in the upper respiratory tract (URT) between children and adults, either presenting with COVID-19 or asymptomatic have yielded inconsistent results. Here, we conducted a retrospective, single center study to address this issue. Patients and Methods 1,184 consecutive subjects (256 children and 928 adults) testing positive for SARS-COV-2 RNA in nasopharyngeal exudates (NP), of whom 424 (121 children and 303 adults) had COVI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Patients infected with the Delta variant were significantly more symptomatic (63.3% (61.7-64.8%)) than those infected with the Alpha variant (40.6% (32.3-49.3%)); p < 0.0001 Fisher's exact test) (Table 1). As the NP viral load can vary among asymptomatic and symptomatic patients and overall, depending on the time of NP sampling after symptom onset [8,9], we compared the viral loads of Alpha/Delta and unvaccinated/vaccinated patients according to symptoms and sampling time after symptom onset. The SARS-CoV-2 viral load of symptomatic patients diagnosed within 4 days after the onset of symptoms was significantly greater than that of asymptomatic patients and those diagnosed later, regardless of vaccination status or variant (Figure 1B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Patients infected with the Delta variant were significantly more symptomatic (63.3% (61.7-64.8%)) than those infected with the Alpha variant (40.6% (32.3-49.3%)); p < 0.0001 Fisher's exact test) (Table 1). As the NP viral load can vary among asymptomatic and symptomatic patients and overall, depending on the time of NP sampling after symptom onset [8,9], we compared the viral loads of Alpha/Delta and unvaccinated/vaccinated patients according to symptoms and sampling time after symptom onset. The SARS-CoV-2 viral load of symptomatic patients diagnosed within 4 days after the onset of symptoms was significantly greater than that of asymptomatic patients and those diagnosed later, regardless of vaccination status or variant (Figure 1B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Some study limitations must be acknowledged: (1) it is uncertain whether the concentration of Spike used in the present work (10 nM) is comparable to those occurring in infected subjects—of note, the viral load of an infected individual varies from 10 2 to 10 13 copies/ml (Costa et al 2021 ) and that the trimeric spike copy number per virion is 26 ± 15 (Yao et al 2020 ): the highest figures should generate in vivo a Spike concentration around 2–7 nM; (2) although our data are compatible with a role of Spike glycosylation in macrophage inflammation, future ad hoc experiments should be performed to prove a causal relationship; (3) the extrapolation of our in vitro data to the complex in vivo setting should be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Aykaç et al detected no difference in viral loads between clinical courses in children. 11 Another study reported higher viral loads in asymptomatic children (p > 0.05) 19 while in contradiction, Kociolek et al reported higher viral loads in symptomatic children (p < 0.001). 20 The discrepancy between different studies may depend on the time the sample was taken.…”
Section: Discussionmentioning
confidence: 96%